2014
DOI: 10.1111/j.1532-950x.2014.12275.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Incisional Complications After Closure of Equine Celiotomies With USP 7 Polydioxanone

Abstract: Overall occurrence of incisional herniation after closure of ventral celiotomies with 7PD was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 22 publications
6
33
1
4
Order By: Relevance
“…Incisional complications after ventral midline celiotomy in horses include infection, herniation, acute dehiscence, suture sinus formation, swelling, drainage, and abscess formation . Incisional herniation occurs frequently, affecting 16% of horses undergoing celiotomy, resulting in significant patient morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…Incisional complications after ventral midline celiotomy in horses include infection, herniation, acute dehiscence, suture sinus formation, swelling, drainage, and abscess formation . Incisional herniation occurs frequently, affecting 16% of horses undergoing celiotomy, resulting in significant patient morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…Braided 6 polyglactin 910 and 7 polydioxanone are produced in other countries, but are not available in the United States. While a recent study reported that use of 7 polydioxanone does not increase the incidence of incisional complications, a prospective case controlled study is required to fully evaluate both KHC and size of square and surgeon's knots using this material …”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in surgical technique and anaesthesia, improvements as measured by the frequency of wound healing problems cannot be seen. Wound healing rates reported up until year 2000 ranged between 7.4% and 61.4% (12,16,19,26,30,39) and after year 2000 between 16% and 62% (4,5,13,27,29,31).…”
Section: Introductionmentioning
confidence: 94%
“…Postoperative risk factors are fever (4,13), leukopenia and postoperative colic (4,17). Smith et al (33) claim an important reduction in wound healing complications when using an abdominal bandage, while other studies do not confirm this finding (17,36).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation